Systematic Evaluation of a Novel 6-dye Direct and Multiplex PCR-CE-Based InDel Typing System for Forensic Purposes - Fan, Haoliang; He, Yitong; Li, Shuanglin; Xie, Qiqian; Wang, Fenfen; Du, Zhengming; Fang, Yating; Qiu, Pingming; Zhu, Bofeng (Frontiers in Genetics, 2022)
Insertion/deletion (InDel) polymorphisms, combined desirable characteristics of both short tandem repeats (STRs) and single nucleotide polymorphisms (SNPs), are considerable potential in the fields of forensic practices and population genetics. However, most commercial InDel kits designed based on non-Asians limited extensive forensic applications in East Asian (EAS) populations. Recently, a novel 6-dye direct and multiplex PCR-CE-based typing system was designed on the basis of genome-wide EAS population data, which could amplify 60 molecular genetic markers, consisting of 57 autosomal InDels (A-InDels), 2 Y-chromosomal InDels (Y-InDels), and Amelogenin in a single PCR reaction and detect by capillary electrophoresis, simultaneously. In the present study, the DNA profiles of 279 unrelated individuals from the Hainan Li group were generated by the novel typing system. In addition, we collected two A-InDel sets to evaluate the forensic performances of the novel system in the 1,000 Genomes Project (1KG) populations and Hainan Li group. For the Universal A-InDel set (UAIS, containing 44 A-InDels) the cumulative power of discrimination (CPD) ranged from 1–1.03 × 10–14 to 1–1.27 × 10–18, and the cumulative power of exclusion (CPE) varied from 0.993634 to 0.999908 in the 1KG populations. For the East Asia-based A-InDel set (EAIS, containing 57 A-InDels) the CPD spanned from 1–1.32 × 10–23 to 1–9.42 × 10–24, and the CPE ranged from 0.999965 to 0.999997. In the Hainan Li group, the average heterozygote (He) was 0.4666 (0.2366–0.5448), and the polymorphism information content (PIC) spanned from 0.2116 to 0.3750 (mean PIC: 0.3563 ± 0.0291). In total, the CPD and CPE of 57 A-InDels were 1–1.32 × 10–23 and 0.999965, respectively. Consequently, the novel 6-dye direct and multiplex PCR-CE-based typing system could be considered as the reliable and robust tool for human identification and intercontinental population differentiation, and supplied additional information for kinship analysis in the 1KG populations and Hainan Li group.